Development of current and future pollutant emissions for Portugal - Sa, Elisa
Air pollutant emissions are a fundamental input for accurate air quality simulations. Therefore, a detailed estimation of current emissions should be performed, mainly for the activity sectors that have higher contributions to emission totals. In order to estimate air quality under climate change at regional scale, it is extremely important to provide the most accurate emission inventories based on the emission scenarios used as input for the global climate models. The Representative Concentration Pathways (RCPs) are the most recent developed emission scenarios. Emission inventories used in air quality simulations at regional scale for future periods should be based on these recent developments. In this sense, an Emission Projections under RCP scenarios (EmiPro–RCP) model was developed to assist the estimation of future emission inventories for GHG and common air pollutants. This paper describes the methodology developed under EmiPro–RCP model and presents the estimation of current and projected emissions for Portugal for CO, PM2.5, PM10, SOx, NOx, NMVOC and NH3, which will be used as input in air quality modeling systems. A comparison between the inventories was performed and the results indicated that all the RCPs scenarios predict a decrease in most of the air pollutant emissions until 2100, with the exception of NH3 that increases. The main decreases are found in the coastal zone of Portugal, mainly in Porto and Lisbon urban areas, while the NH3 increases are located not only in the coastal zone but also in the southern inland of Portugal.